Study of tensiometric properties, microbiological and collagen content in nile tilapia skin submitted to different sterilization methods - Alves, Ana Paula Negreiros Nunes; Lima Júnior, Edmar Maciel; Piccolo, Nelson Sarto; de Miranda, Marcelo José Borges; Lima Verde, Maria Elisa Quezado; Ferreira Júnior, Antônio Ernando Carlos; de Barros Silva, Paulo Goberlânio; Feitosa, Victor Pinheiro; de Bandeira, Tereza Jesus Pinheiro Gomes; Mathor, Monica Beatriz; de Moraes, Manoel Odorico (Cell and tissue banking, 2018)
Tissue bioengineering development is a global concern and different materials are studied and created to be safe, effective and with low cost. Nile Tilapia skin had shown its biological potential as covers for the burn wound. This study evaluates the tilapia skin histological, collagen properties and tensiometric resistance, after treatment by different sterilization methods. Tilapia skin samples were submitted to two sterilization processes: (1) chemical, which consisted in two 2% chlorhexidin baths, followed by sequential baths in increasing glycerol concentrations; and (2) radiation, when glycerolized skin samples were submitted to gamma radiation at 25, 30 and 50 kGy. Microscopic analyzes were performed through Haematoxylin–eosin and Picrosirius Red under polarized light. For tensiometric analysis, traction tests were performed. Glycerol treated skin presented a discrete collagen fibers disorganization within the deep dermis, while irradiated skin did not show any additional change. Throughout the steps of chemical sterilization, there was a higher proportion of collagen with red/yellow birefringence (type I) in the skin samples up to the first bath in chlorhexidin, when compared to samples after the first two glycerol baths ( P < 0.005). However, there was no difference in relation to total collagen between groups. In irradiated skin, there was a larger total collagen preservation when using until 30 kGy ( P < 0.005). Tensiometric evaluation did not show significant differences in relation to maximum load in the groups studied. We concluded that chemical and radiation (25 and 30 kGy) are efficient methods to sterilize Nile Tilapia skin without altering its microscopic or tensiometric characteristics.